Globalization and Gender Studies: Gender Equality Points of SDG's in Effect to Timor Leste's Society Study Case - Azzahra, Fitra Shaumi; Aushafina, Athaya (Global Strategis, 2018)
After gaining independence in 2002, Timor Leste set a goal for its national development as its first order of business. Timor Leste ratified Sustainable Development Goals (SDGs) in order to receive aid and assistance from member states of the United Nations more developed than they were. In 2013, various media outlets and non-governmental organizations highlighted significant growth that Timor Leste showed in matters of gender equality. The country became the only Pacific Asian state to have up to 38 percent of their parliament seats be occupied by women. The high level of women's representation in Timor Leste's government is seen as a way to achieve SDGs and to embody gender equality. However, in reality women still face problems of discrimination on the societal level, as seen from the still all too common occurrences of sexual harassment, as well as accessibility to jobs and education for women which are still far from the standards expected by SDGs. This article argues that the SDG as a form of globalization had not succeeded in homogenizing the culture that applies in Timor Leste. Thus, the top-down structure do not bring any implications towards the needs of women in the country. This article aims to assess the gender-gap phenomenon using three main globalization approaches mainly: homogenized globalization, polarized globalization and the hybrid type of globalization. In the end, this article will also argue that it is more relevant to see current world's culture as a product of hybrid globalization rather than homogenized or polarized globalization especially when it comes to seeing the phenomenon in Third World countries such as Timor Leste.